2017
DOI: 10.1016/j.bbamcr.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of the Saccharomyces cerevisiae cell wall protein Scw4 regulates its activity and influences its covalent binding to glucan

Abstract: Yeast cell wall contains a number of proteins that are either non-covalently (Scw-proteins), or covalently (Ccw-proteins) bound to β-1,3-glucan, the latter either through GPI-anchors and β-1,6-glucan, or by alkali labile ester linkages between γ-carboxyl groups of glutamic acid and hydroxyl groups of glucoses (Pir-proteins). It was shown that a part of Scw4, previously identified among the non-covalently bound cell wall proteins, was covalently attached to wall polysaccharides by a so far unknown alkali sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The exceptions are proteins of the Gas and Crh families known to have the transglycosidase activities required for the proper formation of the cell wall [50], as well as yapsins, aspartic proteases whose role is not yet completely clear. They were reported to participate in proteolytic processing of several cell wall proteins (Scw4, Pir-proteins) and that their activity at least to some extent complements the activity of the Golgi protease Kex2 [14]. At least for Scw4 it has been reported that yapsins also induce its activity [14], but as the exact roles of yapsin substrates are not known, it is difficult to comprehend the role of yapsins, as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exceptions are proteins of the Gas and Crh families known to have the transglycosidase activities required for the proper formation of the cell wall [50], as well as yapsins, aspartic proteases whose role is not yet completely clear. They were reported to participate in proteolytic processing of several cell wall proteins (Scw4, Pir-proteins) and that their activity at least to some extent complements the activity of the Golgi protease Kex2 [14]. At least for Scw4 it has been reported that yapsins also induce its activity [14], but as the exact roles of yapsin substrates are not known, it is difficult to comprehend the role of yapsins, as well.…”
Section: Discussionmentioning
confidence: 99%
“…S. cerevisiae has five yapsin genes, YPS1, YPS2, YPS3/YPS4, YPS6, and YPS7 [42][43][44][45]. The Yps1 protein was found to be a GPI anchored protein located in the cell wall, while the exact localization of other yapsins is not completely clear but they were reported to be responsible for proteolytic processing and activation of several cell wall proteins [14,46]. The method used for orthologue finding in this work did not recognize orthologues of yapsins YPS3 and YPS6 in many species, but it has identified several orthologues of YPS1.…”
Section: In Silico Analysis Of Cell Wall Related Proteins Of Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…S. cerevisiae single scw4 and scw10 mutants are sensitive to cell wall destabilizing agents like Calcofluor white and Congo red, and the scw4scw10 mutant shows a synergistic effect [62]. Grbavac et al [63] demonstrated that Scw4 undergo double processing, by yapsins and Kex2 protease. Processing at the yapsin site significantly lowers the potential for covalent attachment of Scw4 to glucan.…”
Section: Cell Wall Proteins With Enzyme Activitiesmentioning
confidence: 99%
“…Indeed, several regulatory strategies have been implicated in cell wall gene expression, e.g. transcrip onal control imposed by the cell wall integrity (CWI) pathway and other major signaling pathways (Klis et al 2002, Sanz et al 2017, chroma n-based regula on of promoter structure (Barrales et al 2012, Sanz et al 2018, regula on of mRNA stability and localiza on (Catala et al 2012, Cohen-Zontag et al 2019 and proteoly c processing (Gagnon-Arsenault et al 2008, Grbavac et al 2017. In this review, we summarize the current knowledge of how the transcrip on of long non-coding RNAs regulates yeast gene expression and provide arguments in favor of ncRNAs as important new regulators of genes involved in establishing the yeast cell wall structure.…”
Section: Introductionmentioning
confidence: 99%